Synthesis and Characterization of Methoxy-bridged Bis(silylene)tungsten Complexes (Journal of Scientific Research, 2011)
Synthesis of two methoxy bridged bis(silylene) complexes (CpMe4)W(CO)2 {(Et2Si)••OMe••(SiMe2)}(3) and (CpMe)W(CO)2 {(Et2Si)••OMe••(SiMe2)}(4) have been synthesized. Both the compounds contain chiral tungsten center and formed via oxidative addition of an Si-H bond to a coordinatively unsaturated metal center. The complexes were characterized by 1H, 13C, 29Si NMR, IR and elemental analysis. A plausible mechanism of formation is also suggested.Keywords:  Coordinatively unsaturated; Chiral tungsten; Oxidative addition.© 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v4i1.7890J. Sci. Res. 4 (1), 109-118 (2012)